Current Account Balance Estimates for Emerging Market Economies - Prat, Jordi; Medina, Leandro; Thomas, Alun. (Washington, D.C. : International Monetary Fund, 2010)
This paper uses a modified version of the methodology used by the IMF's Consultative Group on Exchange Rate Issues (CGER) to calculate equilibrium current account balances (or ?norms?) for a sample of 33 emerging market economies. We find that the fundamental determinants of the equilibrium current account balances are similar to those identified by the CGER using a sample that also comprises advanced economies. However, the fiscal balance has a considerably stronger impact on current account norms for emerging markets. This paper also offers estimates for the equilibrium current account balances of eleven smaller emerging market economies that are not currently included in the country sample used by the CGER.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet